The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12967-016-1019-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of inflammation and innate immunity in atrophic nonunion fracture

Abstract: BackgroundNonunion is a failure of healing following a bone fracture. Its physiopathology remains partially unclear and the discovery of new mediators could promote the understanding of bone healing.MethodsThirty-three atrophic nonunion (NU) patients that failed to demonstrate any radiographic improvement for 6 consecutive months were recruited for providing serum samples. Thirty-five healthy volunteers (HV) served as the control group. Proteomics studies were performed using SELDI-TOF–MS and 2D-DIGE approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Inflammation is an important cause of delayed union or nonunion of fracture 21 . Previous studies have confirmed that TLR4 can mediate inflammatory response in bone 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is an important cause of delayed union or nonunion of fracture 21 . Previous studies have confirmed that TLR4 can mediate inflammatory response in bone 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A surface-enhanced laser desorption/ionization mass spectrometry (SELDI-MS), relying on selective affinity-based retention of specific molecules on an affinity chip, integrated with MALDI target, represents a promising alternative to gel-based techniques [ 89 ], and is mostly used for analysis of low molecular weight proteins [ 90 ]. Recently, Nedic et al reported an application of SELDI to the analysis of serum fractions obtained by boronic acid- and lectin-affinity chromatography [ 91 ].…”
Section: Part 1 Probing the Structure Of Glycated Proteins By Masmentioning
confidence: 99%
“…Recently, Nedic et al reported an application of SELDI to the analysis of serum fractions obtained by boronic acid- and lectin-affinity chromatography [ 91 ]. SELDI was also successfully used for characterization of glyoxal-derived modifications of bovine erythrocyte superoxide dismutase [ 92 ], for identification of inflammatory biomarkers, and for characterization of innate immunity in atrophic nonunion fracture [ 90 ]. The main advantage of this technique is high sensitivity, i.e., the ability to detect analytes, present in rather low concentrations [ 93 ].…”
Section: Part 1 Probing the Structure Of Glycated Proteins By Masmentioning
confidence: 99%
“…Thus, multiple regulatory mechanisms modulate the effectors of innate immunity to balance between host defense and inflammation. 11 Neutrophils are one of the most prominent effector cells of the innate immune system, 12 which are recruited to the site of infection and exert various antimicrobial effector mechanisms. 13 Antimicrobial peptides (AMPs) are effector molecules of the innate immune system with various activities.…”
Section: Introductionmentioning
confidence: 99%